Study on different solutions to reduce the dynamic impacts in transition zones for high-speed rail - Sañudo, Roberto (2019)
One of the most important factors influencing the track maintenance is the transitions between parts of the track with different vertical stiffness. The dynamic forces in the super-structure, i.e. from rail to ballast/slab and subgrade, including every layer under ballast/slab until natural ground, are influenced by the type of materials, layer configuration and geometry. One way to mitigate track transition problems is to have a more gradual transition with a reduced stiffness differential. The aim of this research is to reduce vertical transiente stresses and displacements under track supports at track transition areas by combining different structural configurations. For this purpose, the train-track dynamic interaction in the transition zones with different vertical stiffness values is analysed using a finite element software. A high-speed train moving on a slab and ballasted track is considered travelling in both directions. The effect of different structural track designs is studied in realistic operation scenarios. The results allow concluding that the sleeper displacements and ballast stresses can be significantly reduced in the transition zones by making small changes in the track structural elements.